(untitled) (Revista Española de Estudios Agrosociales y Pesqueros, 2025)
Since the second half of the twentieth century, the government of Mexico granted support to install aquaculture farms in the center of the country, taking advantage of the forested areas. Since then, aquaculture has become one of the most important activities in the region. However, few aquaculture farmers have managed to develop profitable and sustainable production, despite the growing problems generated by global warming, which have had an impact on the environment and the increase in operating costs. On the other hand, the evaluation of the activities that have been developed to implement more sustainable practices in freshwater aquaculture has not been possible because the satellite accounts do not have updated information. This work determines the factors that have the greatest relationship with the environmental sustainability of freshwater aquaculture in central Mexico, using a questionnaire developed for this research that is based on the FAO Sustainability Assessment of Food Agriculture System, we collected 64 questionnaires applied to aquaculture farmers, as a basis for the development of a proposal aimed at the sustainable practice of freshwater aquaculture. We observe two different groups: the group made up of producers with a high degree of social responsibility and the group of producers who have a medium or low degree of social responsibility. For the first group, environmental sustainability depends on vulnerability and local economy and community development. For the second group, environmental sustainability depends on vulnerability and holistic management. Vulnerability is the factor that affects both groups the most, which is why we propose to train and support producers to reduce risks, constantly checking the temperature, oxygen and quality of the water. It is necessary to bring producers closer to the government and academia to receive permanent advice on disease control and adjustments in feeding, and to build community refuges with controlled waters for fish. It is necessary for fish farmers to be aware that their individual actions have consequences in the community, so that they increase their social responsibility; with that, they can take a more strategic and proactive approach to environmental sustainability.